Uang Elektronik dan Zakat: Kajian Fiqih Kontemporer atas Instrumen Digital dalam Ibadah Harta: Electronic Money and Zakat: Contemporary Fiqh Study on Digital Instruments in Wealth Worship - Mochamad Davin Hukama; Muhammad Yazid (Litera Academica Publishing, 2025)
The rapid development of digital finance has led to new fiqh questions, particularly regarding the use of electronic money (e-money) and its relationship with zakat obligations. This study aims to analyze the position of e-money in Islamic jurisprudence and its zakat implications as a contemporary form of wealth. The method used is a qualitative library research approach with normative and maqashid al-sharia analysis. The findings reveal that e-money constitutes valuable property (mal) subject to zakat when it meets the criteria of ownership, nisab, and haul. Digital zakat platforms also contribute to greater accessibility and transparency in zakat collection and distribution.